Data Driven Digital Innovation in Content Generation and Decision Making: Empowering Content Designers and Artists - Diya Dohare, Abhishek Verma (Journal of Informatics Education and Research, 2024)
This research report delves into the critical significance of content design and provides an overarching perspective on the role of artists in the evolving digital landscape. It explores the transformative impact of digital innovation on content generation, underscoring the importance of strategic decision-making in adopting these advancements. The study’s objectives center on identifying effective strategies, assessing the relevance of AI tools, and examining key factors influencing content creation. The literature review offers a comprehensive evaluation of the content creation industry's dynamics, setting the foundation for the primary quantitative research methodology employed in this study. Data analysis was conducted using SPSS software, incorporating regression analysis, normality tests, and validity assessments to ensure robust findings. The study also examines response rates across diverse demographic variables, such as gender and age, providing nuanced insights into audience perspectives. The discussion highlights the pivotal role of AI tools in revolutionizing content creation, elaborating on their core functionalities and implications. It critically evaluates both the positive and negative impacts of AI, focusing on its applications within the content creation domain. The research concludes by emphasizing how AI technologies empower artists and content creators, reshaping creative processes and fostering innovation in the digital era.